PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 29 PADANG - Irsyada, Irsyada (Departemen Matematika, 2024)
Gaining conceptual understanding is one of the goals of education. However, the results in class VIII of SMP Negeri 29 Padang show that it is at a low stage. The Think-Talk-Write (TTW) cooperative learning model is one way that can be used. Finding out whether eighth graders at SMP Negeri 29 Padang who used the TTW model had a superior understanding of the material compared to those using the direct model was the impetus for this study. This was a quasi-experimental study using a static group design. The sample population consisted of the eighth grade of SMP Negeri 29 Padang. An essay that served as the final exam was the tool used. The t-test was used to analyse the data, and the resulting P-value was 0.040. Thus, H0 was rejected. Using the TTW model, grade eight at SMP Negeri 29 Padang was able to be more effective than using the direct learning model.Keywords – Understanding mathematics concept, TTW, Direct learning